Polyethylene oxide matrix tablet swelling evolution: The impact of molecular mass and tablet composition - Draksler Petra; Mikac Urša; Laggner Peter; Paudel Amrit; Janković Biljana (Acta Pharmaceutica)
This article describes the designing of matrix tablets composed of polyethylene oxides (PEOs) with relative molecular masses of 1 × 106, 2 × 106, and 4 × 106. Percolation thresholds were determined for all of the selected PEO formulations (18, 16, and 12 %, m/m), taking into consideration excipients and tablet surface area which significantly increased the percolation threshold. Moreover, the robustness of the gel layer in PEO matrix tablets was evaluated by magnetic resonance imaging under various mechanical stresses (no flow, 12 mL min−1, and 64 mL−1 of medium flow). Correlations between the percolation threshold and gel thickness (R2 = 0.86), gel thickness and the erosion coefficient (R2 = 0.96) was detected. Furthermore, small-angle X-ray scattering of the selected PEOs detected differences in polymer molecular complexity at the nanoscale. Finally, the ratio of the heat of coalescence to the heat of fusion has confirmed the PEO molecular mass-dependent percolation threshold.